Alterations in Haematological and Clotting Profile of Post-Menopausal Women in Benin City, Nigeria - Ebengho MI; Obazelu PA; Emokpae MA (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2022)
Background: The cessation of ovarian functions at menopause and the accompanying decline in the production of ovarian steroid hormones creates a unique set of health concerns for women. Reductions in sex steroid levels, particularly oestrogen, have been associated with various diseases and conditions, including bleeding disorders, coronary heart disease (CHD), osteoporosis, cognitive dysfunction, urinary incontinence, hot flushes, and mood changes, among others. Objective: To determine changes in haemorheological and clotting profile in post-menopausal women. Methods: Two hundred participants comprising one hundred and fifty post-menopausal women and fifty healthy pre-menopausal control subjects were studied. The investigations carried out include whole blood viscosity, plasma viscosity, fibrinogen concentration, Prothrombin time (PT), Activated partial thromboplastin time with kaolin (APTTK) levels and complete blood count using standard methods. Results: The mean age (p = 0.01), platelet count (p = 0.013), neutrophil (p = 0.03), neutrophil to lymphocyte ratio (p = 0.045) and platelet to lymphocyte ratio (p = 0.044) in postmenopausal women were significantly higher while lymphocyte count (p = 0.004) was significantly lower in postmenopausal compared to premenopausal women. Similarly, plasma oestradiol (p = 0.001), plasma viscosity (p = 0.03), relative blood viscosity (p = 0.03), whole blood viscosity (p = 0.03) and PTTK (p = 0.04) were significantly lower among postmenopausal women compared to premenopausal control subjects. Conclusion: Relative plasma viscosity correlated positively with age. There were significantly lower levels of haemorheological and clotting profile in post-menopausal women. These changes may be due to age or a decline in circulating oestrogen levels.